Cost-effectiveness analysis of standalone trabecular micro-bypass stents in patients with mild-to-moderate open-angle glaucoma in Canada. (3rd April 2019) - Patel, Vardhaman; Ahmed, Ike; Podbielski, Dominik; Falvey, Heather; Murray, Judith; Goeree, Ron
Abstract: Objectives: To estimate the cost-utility of two trabecular micro-bypass stents (TBS) implantation vs standard of care (SOC) in patients with mild-to-moderate open-angle glaucoma (OAG) in the Canadian healthcare setting. Methods: The deterioration in visual field (VF) defect over a 15-year time horizon was tracked using a Markov model with Hodapp-Parrish-Anderson stages of glaucoma (mild, moderate, advanced, severe/blind) and death as health states. Meta-analyses of randomized clinical trials were conducted to estimate the pooled reduction in intraocular pressure (IOP) and medication use due to TBS and SOC. The rate of decline in VF loss was adjusted by the extent of IOP reduction to estimate transition probabilities. Healthcare resource utilization, unit costs (2017 CAD), and progression-related utility scores were obtained by literature review, and medication costs with wastage were obtained from IMS Brogan PharmaStat. The impact of parameter and methodological uncertainty on costs and quality-adjusted life years (QALYs) was examined using probabilistic and 1-way sensitivity analyses. Results: The meta-analysis showed an additional reduction of 1.13 medications/patient and an additional decrease in IOP of –1.10 mmHg at 36 months favoring TBS. TBS strongly dominated medication alone, due to higher improvement in quality-of-life (0.068 QALYs), fewer blind eyes (–0.0031), and a decrease in total healthcare costs of C2, 908.3 per patient over the time horizon (C9, 394.1 TBS vs C12, 302.4 medication alone). Sensitivity analyses showed that results were robust to the uncertainties in model inputs and assumptions. Time-to-dominance was 44 months (3.7 years). Conclusions: The TBS procedure was cost-effective over SOC in a 15-year time horizon, with quality-of-life gains.